Distributed energy storage systems for ramp rate control for solar photovoltaic generation - Liang, Jingyi (2019)
Renewable energy sources, especially solar energy, play an important role in power generation. With the increase in the use of solar energy, it is vital to improve the quality of photovoltaic (PV) generation. The irradiance is one of the key influence factors of PV generation and it will cause the power fluctuation when it changes rapidly. The main aim of this project is to smooth the PV output power with distributed energy storage system by applying the ramp rate control method. To achieve this aim, the structure of the PV cell is classified, and various maximum power point tracking methods are investigated to make sure the PV generators generating the maximum power. A PV module with MPPT control has been implemented in Simulink. A battery model was chosen as the energy storage system in this project and has been implemented with the bidirectional DC/DC converter. Two ramp rate control methods which are low pass filter and moving average method were investigated in this project. The results prove that the use of the ramp rate control method with a battery storage system can help to smooth the PV power and decrease the PV power fluctuation.